Genome-Wide Analysis of Serine Carboxypeptidase-Like Acyltransferase Gene Family for Evolution and Characterization of Enzymes Involved in the Biosynthesis of Galloylated Catechins in the Tea Plant (Camellia sinensis) - Ahmad, Muhammad Zulfiqar; Li, Penghui; She, Guangbiao; Xia, Enhua; Benedito, Vagner A.; Wan, Xiao Chun; Zhao, Jian (Frontiers in Plant Science, 2020)
Tea (Camellia sinensis L.) leaves synthesize and concentrate a vast array of galloylated catechins (e.g., EGCG and ECG) and non-galloylated catechins (e.g., EGC, catechin, and epicatechin), together constituting 8 %-24 % of the dry leaf mass. Galloylated catechins account for a major portion of soluble catechins in tea leaves (up to 75%) and make a major contribution to the astringency and bitter taste of the green tea, and their pharmacological activity for human health. However, the catechin galloylation mechanism in tea plants is largely unknown at molecular levels. Previous studies indicated that glucosyltransferases and serine carboxypeptidase-like acyltransferases (SCPL) might be involved in the process. However, details about the roles of SCPLs in the biosynthesis of galloylated catechins remain to be elucidated. Here, we performed the genome-wide identification of SCPL genes in the tea plant genome. Several SCPLs were grouped into clade IA, which encompasses previously characterised SCPL-IA enzymes with an acylation function. Twenty-eight tea genes in this clade were differentially expressed in young leaves and vegetative buds. We characterized three SCPL-IA enzymes (CsSCPL11-IA, CsSCPL13-IA, CsSCPL14-IA) with galloylation activity towards epicatechins using recombinant enzymes. Not only the expression levels of these SCPLIA genes coincide with the accumulation of galloylated catechins in tea plants, but their recombinant enzymes also displayed β-glucogallin:catechin galloyl acyltransferase activity. These findings provide the first insights into the identities of genes encoding glucogallin:catechin galloyl acyltransferases with an active role in the biosynthesis of galloylated catechins in tea plants.